Determinan Minat Mahasiswa Akuntansi menjadi Akuntan Publik - Amelia Sekar Ayu Pramesti; Nur Fitriana; Dian Puji Puspita Sari (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
The interest of accounting students in Indonesia to pursue a career as public accountants remains low, even though the demand for public accountants continues to increase. According to the Center for the Development of Public Accountants and Appraisers (PPAJP), the growth rate of public accountants in Indonesia is still low, at only 4% per year. The Ministry of Finance's Center for Accounting and Appraisal Services (PPAJP) also released data showing that Indonesia still lacks sufficient public accountants. This is due to the low interest of accounting students in becoming public accountants. This study aims to analyze the influence of self-motivation, intellectual intelligence, financial rewards, and labor market considerations on the interest of accounting students at Muhammadiyah University of Riau in choosing a career as public accountants. The method used is quantitative, collecting primary data through Likert-scale questionnaires. A sample of 247 students was selected using simple random sampling based on the Slovin formula. The data were analyzed using multiple linear regression with SPSS version 25 to test the effect of independent variables on student interest. The results show that self-motivation, intellectual intelligence, financial rewards, and labor market considerations simultaneously and partially have a significant influence on students' interest in becoming public accountants. These variables explain 46.3% of the variation in student interest, while the remaining variation is influenced by other factors beyond this study. The findings provide important contributions to developing strategies to increase public accountant career interest among students.